An Exemplary Story of Growing Temperate Mushroom in Tropical Climate of Rural India: Lessons for Other Startups - Mahantesh Shirur , Shivalinge Gowda N. S. , Chandregowda M. J. , Sunil; Rajesh K. Rana (Indian Journal of Extension Education, 2017)
Mushroom cultivation is a remunerative agribusiness in India and other parts of the world. Being an emerging commercial activity, many startup entrepreneurs are venturing into mushroom cultivation in India. Consumer demand for a particular mushroom variety drives entrepreneurs to create environment controlled facilities for growing that particular mushroom. Growing a temperate mushroom in a tropical climate is advantageous on profit front but it poses several challenges too. The notion of mushroom as a food of elite and several other myths associated with its consumption are impeding its spread to rural areas. A case study of growing temperate mushroom in the tropics of rural India was undertaken. Based on the project cost and cost of growing a temperate mushroom in the countryside of tropical region, the techno-economic feasibility analysis was carried out in this study. The observations in the case study have implications for the mushroom entrepreneurship and mushroom consumption in India and many other tropical countries. Based on the case study, lessons for startup enterprises are also delineated.